Problems of Valuation Activity in The Conditions of Development of Agricultural Market Relations Republic - Dosent., Asadullina Nailya Ramilevna; Normurodov Sarvar Norboy o’g’li (Genius Journals, 2024)
This article examines foreign experience in the development of agriculture and factors influencing the development of agricultural activities, work carried out in this direction in our country in subsequent years. Areas of legislation adopted in our country were also touched upon
Keywords: Agriculture; farming; livestock breeding; sustainable growth